Current controversies in values and science - Elliott, Kelvin C, Ed (Current controversies in philosophy, 2017)
"Current Controversies in Values and Science asks ten philosophers to debate five questions (two philosophers per debate) that are driving contemporary work in this important area of philosophy of science. The book is perfect for the advanced student, building up her knowledge of the foundations of the field while also engaging its most cutting-edge questions. Introductions and annotated bibliographies for each debate, preliminary descriptions of each chapter, study questions, and a supplemental guide to further controversies in involving values in science help provide clearer and richer snapshots of active controversies for all readers."--